A negotiation cloud-based solution to support interoperability among interconnected autonomous microgrids - Cretan, A.; Coutinho, C.; Bratu, B.; Jardim-Goncalves, R. (Proceedings of the 9th IEEE-TEMS International Conference on Intelligent Systems (IS 2018), 2018)
The cooperation of multiple networked microgrids can be one of the best solutions for solving inconsistency between energy production and consumption, which is essential for a more sustainable operation for the manufacturing business. In this paper, we are interested in the collaborative interactions among autonomous microgrids grouped into an alliance to optimise their energy exchange and scheduling as well as ensuring seamless collaboration and interoperability among their distributed systems. Each autonomous microgrid schedules its local power supply and demand, but it may decide to collaborate with other microgrids within the alliance, with minimum information exchange, to better fulfil customer power demands. In this context, this paper proposes a cloud-based collaborative framework where distributed autonomous microgrids can find an optimal solution by negotiating the exchange of energy in order to reduce the need for peak capacity avoiding the risk of blackouts and brownouts. To illustrate this approach, it is described a negotiation scenario in which several microgrids are able to evaluate and generate offers via multi-agent communication protocol.